ANALISIS DAMPAK MODAL INTELEKTUAL, KEPEMILIKAN MANAJERIAL, KEPEMILIKAN INSTITUSIONAL, DAN DEWAN KOMISARIS INDEPENDEN TERHADAP KINERJA KEUANGAN DI MASA DEPAN - Siska Siska; Synthia Madya kusumawati; L. Jade Faliany (Jurnal Manajemen, 2021)
The purpose of this research was to analyze the effects of intellectual capital, managerial ownership, institutional ownership, and the proportion of independent board of commissioners on the company's financial performance. The measurement used was the ratio of probability of return on assets (ROA) of the non-financial services companies listed on the Indonesia Stock Exchange (BEI) for 2016 - 2018 period. The data in this research were audited financial statements and annual reports from 83 eligible non-financial services. 249 samples were used. The data were analyzed by using a descriptive statistical analysis, classical assumption tests, and multiple linear regression tests with the Statistical Package for Social Sciences (SPSS) version 20. The results showed that the intellectual capital variable had a positive effect on the company's financial performance, while the managerial ownership and institutional ownership variables had no effect on the company's financial performance, and the proportion of independent commissioner variable had a negative effect on the company's financial performance. The abstract contains a brief description about overall article’s, problems and research objectives, research methods, research results, conclusions and suggestions.